2020
DOI: 10.22460/project.v3i3.p359-366
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Transitivity Process of Students’ Descriptive Texts

Abstract: This research analysis transitivity process of the descriptive text written by the students at seventh grade in junior high school. The objectives of this research is to find out the use of transitivity process of students’ descriptive texts and to find out the most dominant of transitivity process. This reseach analyzed 60 sentences taken from eight descriptive texts written by the students. The researcher used descriptive quantitative method to analyzed the transitivity process. The result of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, the sentences found in the textbook were also common in terms of relational possessive processes, such as has, have, and had. The finding is in accordance with a study by Apendi & Mulyani (2020); Imanuri (2019), which revealed that several adjectives involve when telling a descriptive text, namely descriptive adjectives, demonstrative adjectives, and positive adjectives. The relational transitivity process is used in the descriptive text to explain and identify (identifying) what they described.…”
Section: Table 7 the Existential Example Of Existential Process In Th...supporting
confidence: 92%
“…Meanwhile, the sentences found in the textbook were also common in terms of relational possessive processes, such as has, have, and had. The finding is in accordance with a study by Apendi & Mulyani (2020); Imanuri (2019), which revealed that several adjectives involve when telling a descriptive text, namely descriptive adjectives, demonstrative adjectives, and positive adjectives. The relational transitivity process is used in the descriptive text to explain and identify (identifying) what they described.…”
Section: Table 7 the Existential Example Of Existential Process In Th...supporting
confidence: 92%
“…The six categories of transitivity processes that Halliday (2004) distinguishes are material, mental, relational, behavioral, existential, and verbal processes. (Apendi & Mulyani, 2020).…”
Section: Transitivitymentioning
confidence: 99%
“…The findings and analysis show that the relational process is the most dominant process type in ideational metafunction which was found in Dinas Kebudayaan, Kepemudaan Olahraga There are similarities between this research and other research. Harwiyati (2016) Apendi and Mulyani (2020) found that material process is the dominant process in analysis of transitivity system of students' descriptive texts and Halima (2019) also material process which often appeared in a short story. Meanwhile, the study conducted by Wulansari and Waluyo (2016) behavioral process is more often appeared than others which embbeded in a poem.…”
Section: Dominant Process Typementioning
confidence: 99%